The role of prognostic biomarkers and their implications in early detection of preeclampsia: A systematic review. (March 2023) - Parthasarathy, Srividya; Soundararajan, Prathyusha; Sakthivelu, Meenakumari; Karuppiah, Kanchana Mala; Velusamy, Palaniyandi; Gopinath, Subash C.B.; Pachaiappan, Raman
Abstract: Preeclampsia is a multisystemic condition causing severe implications in mothers and children suffering from proteinuria and gestational hypertension. Globally, there is an upsurge in morbidity and mortality due to preeclampsia and its complications such as hypertension, endothelial dysfunction, various cardiovascular diseases and proteinuria. Research and meta-analysis on preeclampsia are emphasized as complete understanding about its underlying cause remains to be obscure. The occurrence of preeclampsia is indicated by the presence of elevated levels of methylenetetrahydrofolate reductase (MTHFR), homocysteine and asymmetric dimethylarginine (ADMA) which are well known to be associated with risk factors and are therefore considered as prognostic biomarkers for identifying women with preeclampsia at a very early stage. Elevated levels of these biomarkers cause chronic inflammation which impairs endothelial function. Endothelial dysfunction has been notably prominent in studies addressing the complications of preeclampsia such as cardiovascular disease (CVD). Various analytical techniques have been employed in the accurate screening and quantification of these molecules which is crucial in understanding molecular mechanisms underlying the pathophysiology of various preeclamptic complications. The epigenetic modifications in certain genes not only alter the biosynthesis and regulation of MTHFR, homocysteine and ADMA but also act as individual markers leading to conditions that heighten preeclampsia, giving rise to cardiovascular risk during and after preeclampsia. Therefore, multiple biomarkers are often desired because of their synergistic effect to enhance clinical efficiency. This review focuses on the metabolic links between MTHFR, homocysteine and ADMA, their role as preeclampsia risk predictors, their lowering mechanisms, strategies that incorporate multiple markers and their importance over individualistic biomarkers. In conclusion, the use of a multiple biomarker approach with MTHFR SNPs, homocysteine and ADMA can contribute to the advanced prediction of preeclampsia and its complications. Highlights: Preeclampsia-multisystemic condition with severe implications in mother and child. Research on preeclampsia is emphasized that understanding remains to be obscure. Preeclampsia is by the presence of elevated levels of MTHFR, homocysteine and ADMA. Elevation of these biomarkers cause chronic inflammation & endothelial malfunction. This systematic review provides insights on the above scenario and their relations.